THE POLITICAL NOVEL AND THE POLITICIZATION OF THE NOVEL - Peprník, Michal (Bohemica Olomucensia, 2022)
The paper argues that we should differentiate between explicitly and implicitly political novels and the politicization of novels, the latter being a result of symptomatic interpretation (Culler). This differentiation helps preserve the discriminating sense of (sub) genre distinctions as an awareness of these categories makes the reader more sensitive to all kinds of manipulations of genre rules. Political novels should be recognized by the predominance of political motifs (setting, characters, themes, dialogue, agenda and conflict). Implicitly political novels lack explicit political motifs, but advocate the need for some kind of political commitment and political reform. The individual categories are illustrated using examples of 19th-century American novels.
Keywords: Political novel; politicization of literature; subgenre; symptomatic interpretation; 19th-century American novels